IMPROVING STUDENT’S LEARNING OUTCOMES BY USING MICROSOFT EXCEL AND STATISTICAL PROGRAM OF SOCIAL SCIENCE - Herlina Herlina (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
AbstractOne of the factors causing the low score of student learning outcomes Statistics and Probability on midterm exams is that during practice or studying on their own, students feel the complexity of solving questions about data analysis in Statistics and Probability courses and the difficulty of obtaining confirmation of correct answers. This encourages to find alternative solutions. One of them is using Excel and Statistical Program of Social Science (SPSS) software in Statistics and Probability learning. The purpose of this research is to improve the learning outcomes of Statistics and Probability using Excel and SPSS software. The method used in this research is the One-Group Pretest-Posttest Design. Samples were selected using the Cluster Random Sampling technique. To see if there is an increase in learning outcomes, it is done by comparing the average learning outcomes of the midterm exams (before using Excel and SPSS software) and final semester exams (after using Excel and SPSS software). The results of the Wicoxon test showed Asymp. Sig. (2-tailed) 0.000 less than 0.05, so it can be concluded that the pretest and posttest means are significantly different. This shows that there is an increase in learning outcomes before and after learning using Excel and SPSS software, so it is concluded that student learning outcomes in Statistics and Probability courses can be improved through learning by using Excel and SPSS software. Keywords: excel; learning outcomes; software; SPSS Abstrak Salah satu faktor penyebab rendahnya nilai hasil belajar Statistik dan Probabilitas mahasiswa pada ujian tengah semester disebabkan pada saat latihan atau belajar sendiri. Mahasiswa merasakan rumitnya penyelesaian soal tentang analisis data pada mata kuliah Statistik dan Probabilitas dan sulitnya memperoleh konfirmasi jawaban benar. Hal ini mendorong untuk menemukan alternatif solusi. Salah satu alternative solusi adalah memanfaatkan software Excel dan Statistical Program of Social Science(SPSS) dalam pembelajaran Statistik dan Probabilitas.Tujuan penelitian ini adalah untuk meningkatkan hasil belajar Statistik dan Probabilitas menggunakan software Excel dan SPSS. Metode yang digunakan dalam penelitian ini adalah One-Group Pretest-Posttest Design. Sampel dipilih dengan teknik Cluster random Sampling. Untuk melihat apakah ada peningkatan hasil belajar, dilakukan dengan membandingkan rata-rata hasil belajar ujian tengah semester (sebelum memanfaatkan software Excel dan SPSS) dan ujian akhir semester (setelah memanfaatkan software Excel dan SPSS). Hasil uji Wicoxon menunjukkan Asymp. Sig. (2-tailed) 0,000 kurang dari 0,05 sehingga disimpulkan bahwa rata-rata pretest dan posttest berbeda  secara signifikan. Hal ini menunjukkan bahwa terjadi peningkatan hasil belajar sebelum dan sesudah pembelajaran memanfaatkan software Excel dan SPSS, sehingga disimpulkan bahwa hasil belajar mahasiswa pada mata kuliah Statistik dan Probabilitas dapat ditingkatkan melalui pembelajaran dengan memanfaatkan software Excel dan SPSS.Kata kunci: excel; hasil belajar; software; SPSS.